EVALUATION OF ANTI-ASTHMATIC ACTIVITY OF ETHANOLIC EXTRACT OF EPHEDRA GERARDIANA WALL IN MICE BY OVALBUMIN INDUCED METHOD - B.Chaitanya,; Raviteja Sagi, S M; P.Shashikanth,; K.KARUNAKAR, (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Ephedra gerardiana Wall. have anti-inflammatory properties and in some instances smooth muscles relaxing effects. Since inflammation and airway smooth muscle contraction are two major components of asthma, the present study is going to investigate the effects of Ephedra gerardiana Wall. on airway inflammation and airway resistance in a mouse model of asthma. Mice were sensitized and challenged with ovalbumin (OVA) and treated intraperitoneally with Ephedra gerardiana Wall. The effect of Ephedra gerardiana Wall. was tested on airway inflammation, air way resistance and the increase of intracellular calcium in bronchial smooth muscle cells. In the present study we are going to evaluate the extent of lung inflammation according to Helsinki convention,OVA-specific immunoglobulin-E (IgE) titre by ELISA and histopathological studies. Ephedra gerardiana wall at 100 and 200 mg·kg–1 significantlyreduced the total number of cells (p < 0.001; n = 6),eosinophils (*** p < 0.001)in BAL compared with the untreated group of OVA sensitised mice. Keywords: Asthma, Inflammation, Ephedra gerardiana, Ovalbumin induced mice model, Immunoglobulin E.